Anti-fibrotic Potential of AT2 Receptor Agonists - Wang, Yan; Del Borgo, Mark; Lee, Huey W.; Baraldi, Dhaniel; Hirmiz, Baydaa; Gaspari, Tracey A.; Denton, Kate M.; Aguilar, Marie-Isabel; Samuel, Chrishan S.; Widdop, Robert E. (Frontiers in Pharmacology, 2017)
There are a number of therapeutic targets to treat organ fibrosis that are under investigation in preclinical models. There is increasing evidence that stimulation of the angiotensin II type 2 receptor (AT2R) is a novel anti-fibrotic strategy and we have reviewed the published in vivo preclinical data relating to the effects of Compound 21 (C21), which is the only nonpeptide AT2R agonist that is currently available for use in chronic preclinical studies. In particular, the differential influence of AT2R on extracellular matrix (ECM) status in various preclinical fibrotic models is discussed, and novel in vitro data on the anti-fibrotic effects of C21 is also presented. Collectively, these studies demonstrate that pharmacological AT2R stimulation using C21 decreases organ fibrosis, which has been most studied in the setting of cardiovascular and renal disease. In addition, AT2R-mediated anti-inflammatory effects may contribute to the beneficial AT2R-mediated anti-fibrotic effects seen in preclinical models.